2005
DOI: 10.1107/s1600536805035695
|View full text |Cite
|
Sign up to set email alerts
|

X-ray powder refinement of a natural garnet from Diamantina, Minas Gerais, Brazil

Abstract: The chemical composition, [Mg0.015 (2),Al1.20 (2),Si2.99 (1),Ca3.00 (2),Ti0.027 (3),Mn0.017 (3), Fe0.75 (3)]O12 (magnesium alumin­ium silicon calcium titanium manganese iron dodeca­oxide), of a natural garnet collected at Diamantina, Minas Gerais, Brazil was determined by electron microprobe analysis. The structure refinement from X‐ray powder data is insensitive to the small amounts of Ti, Mn and Mg. The determined cation distribution using the Rietveld method is {Ca32+}[Al1.338 (8)3+,Fe0.662 (8)3+](Si34+)O12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Therefore, disagreements between the real and calculated Al sofs should be also most probably treated as a consequence of some polyhedral distortions and crystal disordering and their longer 〈 Y –O〉 distances, as well. Nevertheless, this is not so unusual phenomenon because more or less discrepancies between SCXRD, XRPD, and HRPXRD methods with chemical and EMPA compositions are already observed elsewhere (see Gali, 1984; Resende and Fernandes, 2005; Antao and Klincker, 2013).…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…Therefore, disagreements between the real and calculated Al sofs should be also most probably treated as a consequence of some polyhedral distortions and crystal disordering and their longer 〈 Y –O〉 distances, as well. Nevertheless, this is not so unusual phenomenon because more or less discrepancies between SCXRD, XRPD, and HRPXRD methods with chemical and EMPA compositions are already observed elsewhere (see Gali, 1984; Resende and Fernandes, 2005; Antao and Klincker, 2013).…”
Section: Resultssupporting
confidence: 51%
“…Also, Diamantina disordering is of different kind than Meka Presedla (previously explained within discussion about criterion (II); Supplementary Material 8) because it has longer 〈 Y –O〉 and 〈 X ′–O〉 but shorter 〈 X ″–O〉 and 〈 X –O〉 distances than it should be expected from its chemical composition. As shown by Resende and Fernandes (2005), in this grandite the arrangement of the cations around the O atom is best described as a highly distorted tetrahedral, due that the O atom is displaced by 0.267(7) Å from the plane defined by Ca 2+ , Si 4+ , and Y = Al 3+ /Fe 3+ .
Figure 9.(Color online) Comparison of the Fe 3+ and Al 3+ variations over the octahedral sites by the octahedral average 〈 Y –O〉 distances for the Meka Presedla rhombohedral (blue) and orthorhombic Fddd (orange) space groups, Diamantina cubic space group (green), and Munam triclinic space group (red) grandites.
…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…As pre vi ously shown by Tanèiae et al (2020), there are only two fer ric grossular sam ples found in the avail able lit er a ture, which have very sim i lar chem i cal com po si tions to our sam ple. These are Grs 60 Adr 38 -Grs 67 Adr 33 from Dia man tina, Brazil (cubic Ia63d space group, Resende and Fernandes, 2005), and Grs 67 Adr 33 from Munam, North Ko rea (triclinic I61 space group, Takéuchi et al, 1982). How ever, these three fer ric grossular gar nets are ob vi ously struc tur ally very dif fer ent be tween each other, as all of them crys tal lize not only in dif fer ent space groups, but also in dif fer ent crys tal lo graphic sys tems.…”
Section: Polyhedral Distortions and Structural Disordering Between Th...mentioning
confidence: 99%
“…The mean-square amplitudes of vibration of the oxygen atom are higher in a direction approximately perpendicular to the bond. In a Rietveld refinement, a natural garnet showed similar behavior (Resende and Fernandes, 2005).…”
Section: Resultsmentioning
confidence: 83%